Continuous postive airways pressure treatment by a face chamber in idiopathic respiratory distress syndrome. Issue 1 (January 1976) - Ahlström, H; Jonson, B; Svenningsen, N W
Abstract : Continuous positive airways pressure treatment by a face chamber in idiopathic respiratory distress syndrome. During a 3-year period 45 infants with idiopathic respiratory distress syndrome (IRDS) requiring ventilatory support were treated in the neonatal unit. Continuous positive airways pressure (CPAP) via the face chamber was applied as initial therapy in 39 infants and during weaning from initial intermittent positive pressure ventilation (IPPV) treatment in 5 infants, whereas 1 infant received IPPV only. Among the 39 infants initially treated with CPAP 9 required IPPV as well. The overall survival rate was 37/45 or 82%. Incapacity to hyperoxygenate while breathing 100% oxygen was the indication for CPAP while occurrence of apnoeic attacks was the indication for IPPV. Pao2 during the hyperoxia test before ventilatory support was less than 50 mmHg in 10 infants and between 50 and 105 mmHg in 35 infants. Surviving infants were followed up with neurological and developmental control examinations as well as chest x-ray, and in several infants pulmonary function tests. 3/37 infants had moderate neurological sequelae and only 1/37 infants developed bronchopulmonary dysplasia. No deleterious effects of the face chamber were seen. As the face chamber is a noninvasive and easily applied technique for CPAP therapy without hazards, it is proposed that it should be used at a still earlier stage of IRDS in order to lesson the need for IPPV treatment and to increase the neurological and lung functional quality of survival.